POSITIVE AND NEGATIVE IMPACTS OF ONLINE LEARNING FOR MINORS - Gerardus Gegen (SEAN Institute, 2021)
This research was conducted in order to see more clearly the impact received by minors due to drastic changes in the learning system in Indonesia since the Covid-19 pandemic hit. In the midst of the online learning process which is carried out simultaneously, this certainly has a very, very impact on students who undergo it, including children who should be more restricted in their use in order to maintain the physical and psychological condition of the child. Therefore, we work closely with parents to see how children are developing in the face of this changing learning system and what impact they see as parents. From this we see that online learning has a very, very impact on the lives of the children themselves